Ecologia de riachos : interação peixe-habitat e adequação de um índice baseado na assembleia de peixe (IBP) no alto da bacia do rio Paraná, Brasil Central. - Fialho, Afonso Pereira (2008)
The different ecological approaches are based theoretically on the existence of interactions between aquatic and terrestrial ecosystems, especially considering their functionality and composition. Parts of this theoretical grounding are the River continuum concept, the importance of limnological variables to the functioning and structure of these ecosystems and the spatial and temporal scales of variability influencing on the distribution of aquatic and terrestrial organisms. In order to explain the relationship between fish habitat in streams and creeks at different scales, many studies were conducted in South America since the 90?s, but in the sub-basin of the João Leite River, Goiás State, this study is the first. The unrestrained search for regional growth encouraged by the state government agencies favored the disorderly occupation of different ecosystems, of which little or almost nothing is known about its function and structure, including its biotic elements such as the fish assemblages. The different ways of evaluating the quality of aquatic ecosystems used in Brazil rely on the collection, measurement and comparison of chemical elements stipulated in rules and laws of environmental agencies. In this type of evaluation, the biological elements (in this case the fish and others), as well as their interactions with the habitat, are not included. The purpose of this study is the ordination of biological and environmental data, aiming to i) determine which of natural or anthropogenic environmental variables are associated with the composition and structure of the fish assemblages and ii) adjust the index based on fish (IBP), checking the result obtained with data collected independently and in another region of the same basin, but with similar characteristics.